2007
DOI: 10.1016/j.ydbio.2007.09.038
|View full text |Cite
|
Sign up to set email alerts
|

Noggin is required for normal lobe patterning and ductal budding in the mouse prostate

Abstract: Mesenchymal expression of the BMP antagonist NOGGIN during prostate development plays a critical role in pre-natal ventral prostate development and opposes BMP4-mediated inhibition of cell proliferation during postnatal ductal development. Morphologic examination of newborn Noggin-/- male fetuses revealed genitourinary anomalies including cryptorchidism, incomplete separation of the hindgut from the urogenital sinus (UGS), absence of the ventral mesenchymal pad, and a complete loss of ventral prostate (VP) bud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
71
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 59 publications
(79 citation statements)
references
References 47 publications
7
71
0
Order By: Relevance
“…BMP4 inhibits budding in UGS organ culture and this effect can be overcome by the BMP antagonist NOGGIN (Cook et al, 2007;Lamm et al, 2001). Detailed analysis of the Bmp4 null heterozygote showed that functional haploinsufficiency for Bmp4 was associated with increased prostatic budding (Almahbobi et al, 2005) and increased indices of branching morphogenesis (Lamm et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…BMP4 inhibits budding in UGS organ culture and this effect can be overcome by the BMP antagonist NOGGIN (Cook et al, 2007;Lamm et al, 2001). Detailed analysis of the Bmp4 null heterozygote showed that functional haploinsufficiency for Bmp4 was associated with increased prostatic budding (Almahbobi et al, 2005) and increased indices of branching morphogenesis (Lamm et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Epidermal growth factor (Saito and Mizuno, 1997), homeobox genes (Podlasek et al, 1997;Warot et al, 1997), and both low-dose and high-dose estrogens (vom Saal et al, 1997) have been shown to influence budding, but the mechanisms by which these effects occur is unclear. The bone morphogenetic proteins (BMPs) 4 and 7 (Cook et al, 2007;Grishina et al, 2005) and wingless integration site A (WNT5A; unpublished observations) can directly inhibit bud formation while hedgehog (Hh) signaling has been implicated as a positive regulator of budding (Podlasek et al, 1999;Lamm et al, 2002;Doles et al, 2006). What remains to be determined is how these positive and negative influences are orchestrated to yield the reproducible pattern and quantity of buds that form on select surfaces of the male mouse UGS during fetal development.…”
Section: Introductionmentioning
confidence: 99%
“…Of note, BMP7 inhibits epithelial proliferation, branching morphogenesis and ductal budding in the normal development of the prostate, and is also associated with decreased Notch signaling (Grishina et al, 2005), a critical pathway during morphogenesis of epithelial tissues. In this context, the BMP antagonist Noggin can have a key regulatory role in BMP4 and BMP7 action in tissue epithelial stem cells (Cook et al, 2007). Strikingly, the BMP2/7 heterodimer was a more potent inhibitor of TGFb signaling than its BMP2 and BMP7 homodimeric counterparts.…”
Section: Bmp2/7 Inhibits the Breast Cancer Stem Cell Subpopulation Jtmentioning
confidence: 99%
“…5; supplementary material). Several studies describing early murine prostate development (Allgeier et al, 2010(Allgeier et al, , 2009Cook et al, 2007) have instructed modifications to the ontology. Numerous prostate buds develop from the PLUR epithelium in distinct locations (Fig.…”
Section: Introductionmentioning
confidence: 99%